Dynamic allocation of microservices for virtual reality content delivery to provide quality of experience support in a fog computing architecture - Alencar, Derian; Oliveira, Helder; Rosário, Denis (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2023: Anais do XXXVI Concurso de Teses e Dissertações, 2023)
Virtual Reality (VR) content is gaining popularity and allowing users to immerse themselves in a new world over the Internet. However, the high-demand for resources and the low latency requirements of VR services require changes in the current 5G networks to deliver VR with quality assurance. Microservices present a suitable model for deploying services at different levels of a 5G fog computing architecture for managing traffic and providing Quality of Experience (QoE) guarantees to VR clients. However, finding the most suitable fog node to allocate microservices for VR clients in QoE-aware 5G scenarios is a difficult task. This article proposes a QoE VR-based mechanism for allocating microservice dynamically in 5G architectures, called Fog4VR. Fog4VR determines the optimal fog node to allocate the VR microservice based on delay, migration time, and resource utilization rate. This article also presents the INFORMER, an integer linear programming model aiming to find the optimal global solution for microservice allocation. Results obtained with INFORMER serve as a baseline to evaluate Fog4VR in different scenarios using a simulation environment. Results demonstrate the capabilities of Fog4VR compared to existing mechanisms in QoE, migration time, fairness index, and terms of cost.